2011
DOI: 10.1007/s10584-011-0020-1
|View full text |Cite
|
Sign up to set email alerts
|

Tropical cyclones, climate change, and scientific uncertainty: what do we know, what does it mean, and what should be done?

Abstract: The question of whether and to what extent global warming may be changing tropical cyclone (TC) activity is of great interest to decision makers. The presence of a possible climate change signal in TC activity is difficult to detect because interannual variability necessitates analysis over longer time periods than available data allow. Projections of future TC activity are hindered by computational limitations and uncertainties about changes in regional climate, large scale patterns, and TC response. This rev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
26
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 42 publications
(26 citation statements)
references
References 157 publications
(295 reference statements)
0
26
0
Order By: Relevance
“…The opposing thermodynamic and dynamic effects in individual basins may cause uncertainty and difficulty in future regional scale TC projections (Grossmann and Morgan 2011).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The opposing thermodynamic and dynamic effects in individual basins may cause uncertainty and difficulty in future regional scale TC projections (Grossmann and Morgan 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Camargo (2013) found that among the 14 CMIP5 models analyzed, the model with the highest horizontal resolution performed the best on global TC activity. The difficulty and uncertainty of future TC projections in individual basins may be attributed to both computational limitations and the opposing thermodynamic and dynamic effects (Grossmann and Morgan 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Analysis of observational records also produced conflicting interpretations of historical trends of TC intensity for the WNP basin (Grossmann and Morgan 2011). Some studies argued that the overall TC intensity and the number of intense TCs show significant increasing trends with tropical ocean warming (Emanuel 2005;Webster et al 2005), whereas others raised a counterargument that decadal variations are more dominant than specific trends (Chan 2006(Chan , 2008.…”
Section: Introductionmentioning
confidence: 99%
“…Bender et al (2010) also find an overall decrease in TC counts but a substantial increase in the frequency of the most intense hurricanes. A review article by Grossmann and Morgan (2011) describes the difficulty in projecting future changes in TC activity and emphasizes both computational limitations and the uncertainty when projecting the regional response to climate change, as both thermodynamic and dynamic responses would affect the severity of future hurricane seasons. A review article by Grossmann and Morgan (2011) describes the difficulty in projecting future changes in TC activity and emphasizes both computational limitations and the uncertainty when projecting the regional response to climate change, as both thermodynamic and dynamic responses would affect the severity of future hurricane seasons.…”
Section: Introductionmentioning
confidence: 99%